The negative chronotropic effects of (±)-propranolol and (±)-4-NO2-propranolol in the rat isolated right atrium are due to blockade of the 6-nitrodopamine receptor - Oliveira, Denis Lima; Cardoso, Vinicius Francisco; Britto-Júnior, Jose; Fuguhara, Vivian; Frecentese, Francesco; Sparaco, Rosa; Santagada, Vincenzo; Caliendo, Giuseppe; Pupo, André Sampaio [UNESP]; Antunes, Edson; De Nucci, Gilberto (Springer Nature, 2024)
The positive chronotropic action induced by 6-nitrodopamine (6-ND) is selectively blocked by β1-adrenoceptor antagonists at concentrations that do not affect the positive chronotropic effect induced by dopamine, noradrenaline, and adrenaline. Here, the effects of (±)-propranolol, (±)-4-NO2-propranolol, and (±)-7-NO2-propranolol were investigated in the rat isolated right atrium. The atrium was mounted in glass chambers containing gassed (95%O2:5%CO2) and warmed (37 °C) Krebs–Henseleit’s solution, and the isometric tension registered (PowerLab system). (±)-Propranolol, (±)-4-NO2-propranolol, and (±)-7-NO2-propranolol caused concentration-dependent falls in the spontaneous atrial frequency (pIC50: 4.80 ± 0.10, 4.64 ± 0.10, and 4.95 ± 0.10, respectively). The calculated pA2 values for (±)-propranolol, (±)-4-NO2-propranolol, and (±)-7-NO2-propranol on noradrenaline-induced positive chronotropism were 8.44 ± 0.08, 6.41 ± 0.07, and 9.21 ± 0.29, respectively. The positive chronotropism induced by 6-ND (10 pM) was blocked by (±)-propranolol (1 µM) and (±)-4-NO2-propranolol (30 nM), whereas (±)-7-NO2-propranolol (1 µM) had no effect on 6-ND-induced responses. The pIC50 of (±)-propranolol, (±)-4-NO2-propranolol, and (±)-7-NO2-propranolol were significantly shifted to the right in L-NAME-treated atria. The discrepancy between pA2 values of (±)-propranolol and its respective pIC50 indicates that the falls in atrial rate induced by (±)-propranolol should not be attributed to b-adrenergic antagonism. The reduced chronotropism by (±)-propranolol was unaffected by the sodium channel inhibitors tetrodotoxin and lidocaine but that was abolished in atria pre-treated with (±)-4-NO2-propranolol. The finding that (±)-propranolol reduces spontaneous atrial rate only in concentrations that affect 6-ND-induced positive chronotropism confirms the role of this catecholamine as an endogenous modulator of heart chronotropism. (±)-4-NO2-Propranolol behaves as a selective antagonist of 6-ND in the rat isolated atrium.
Keywords: Beta-blocker; Catecholamines; L-NAME; Stereoselectivity